The will of the people? The responsiveness of UK MPs during the EU withdrawal process (2016-2019) - Stafford, Christopher (2023)
The impact of the 2016 EU referendum result on UK politics was as dramatic as it was unexpected. Instead of endorsing the status quo, it forced a significant change in policy direction that most of the political class disagreed with. However, this rare example of direct delegation to UK voters did little to alter the strong and persistent perceptions among them that their MPs do not care what they think. On the contrary, it appeared to exacerbate such sentiments and reinforce the beliefs of voters that their representatives are primarily motivated by other factors.